How to adopt technologies in home care: a mixed methods study on user experiences and change of home care in Finland - Minna Anttila; Juha Koivisto; Minna-Liisa Luoma; Heidi Anttila (BMC Health Services Research, 2023)
Abstract Background There is a need for better adoption of technology to meet the needs of home care professionals, older people, and informal caregivers. Methods Mixed methods were used to describe and analyse quantitative and qualitative data in a Finnish governmental programme called KATI. The study was three-fold: it 1) listed what kinds of technologies were piloted and deployed in a national study, 2) provided information from the perspectives of home care professionals about requirements to use technology by using focus-group interviews, and 3) assessed experiences of how the adoption of technology changes work and work processes over time by using repeated surveys. Informants in interviews (n = 25) and surveys (n = 90) were home care professionals, who also described the perspectives of older people and informal caregivers. The conceptual models framing the study were adapted from the Technology Acceptance Model and DirVA PROVE-IT. Results There were 80 technology pilots, in which variety of technologies were followed in home care. Familiarity with, commitment to and understanding of technology benefits were considered to be requirements for the technology to be used. The adoption of technology provided new skills and information about older people’s wellbeing, realisation of treatment and new possibilities in home care. It developed new procedures to focus on older people’s needs and motivated professionals by gained concrete aid. It enabled them to leave out some concrete procedures as unnecessary. On the other hand, there were also pessimistic and negative experiences when technology use provided nothing new or did not change anything. Conclusions The adoption of technology is dependent on the technology and its integration into the prevailing service practice. When they both work, it is possible to leave out unnecessary procedures in care, allocate resources and save time. It is possible to be aware of older people’s safety and how they cope at home, find new ways to get involved in older people’s lives, gain insight, and make changes at work. Continuous on-site training, modifications in service practices and communication throughout organisations is needed.